Comparison of Laboratory Data between Children with Kawasaki Disease and COVID-19 - Xiao-Ping Liu; Ying-Hsien Huang; Yuh-Chyn Tsai; Shih-Feng Liu; Ho-Chang Kuo (MDPI AG, 2022)
Background: Coronavirus disease 2019 (COVID-19) has been an emerging, rapidly evolving situation in China since late 2019 and has even become a worldwide pandemic. The first case of severe childhood novel coronavirus pneumonia in China was reported in March 2020 in Wuhan. The severity differs between adults and children, with lower death rates and decreased severity for individuals under the age of 20 years. Increased cases of Kawasaki disease (KD) have been reported from New York City and some areas of Italy and the U.K., with almost a 6-10 times increase when compared to previous years. We conducted this study to compare characteristics and laboratory data between KD and COVID-19 in children. Methods: We obtained a total of 24 children with COVID-19 from a literature review and 268 KD cases from our hospital via retrospective chart review. Results: We found that patients with KD have higher levels of white blood cells (WBCs), platelets, neutrophil percentage, C-reactive protein (CRP), procalcitonin, and aspartate aminotransferase (AST) and a higher body temperature, while patients with COVID-19 have a higher age, hemoglobin levels, and lymphocyte percentage. After performing multiple logistic regression analysis, we found that age, WBCs, platelets, procalcitonin, and AST are identical markers for distinguishing COVID-19 from KD in children. Conclusion: In this COVID-19 pandemic period, clinicians should pay attention to children with COVID-19 infection when high WBC, platelet, procalcitonin, and AST values are present in order to provide early diagnosis for KD or multisystem inflammatory syndrome in children (MIS-C).